Levoglucosan and its hydrolysates via fast pyrolysis of lignocellulose for microbial biofuels: A state-of-the-art review. (May 2019) - Jiang, Li-Qun; Fang, Zhen; Zhao, Zeng-Li; Zheng, An-Qing; Wang, Xiao-Bo; Li, Hai-Bin
Abstract: Fast pyrolysis, which is comparable with the enzyme or acid hydrolysis, should be considered for further development for fermentable levoglucosan (LG) production. This manuscript offers a broad review of the current status and future research perspectives of LG and its hydrolysates production from lignocellulosic biomass by fast pyrolysis for fermentation. The utilization, distribution and formation paths of LG from cellulose are presented. In consideration of the complexity of cellulose structure and lignocellulosic components, the influence of the major individual components (cellulose, hemicellulose, lignin and ash) and the structural properties (particle size, degree of polymerization and crystallinity) on the LG formation are reviewed. Aiming to further improve the yield of LG and the fermentability of pyrolysate, a number of pretreatment methods (e.g. hot-water pretreatment, acid pretreatment, acid impregnation) prior to fast pyrolysis, hydrolysis of LG and detoxification before fermentation, and microbial production of valuable products are also discussed in detail. At last, a brief conclusion for the challenge in this topic is provided. The low content of LG and the presentence of inhibitors to biocatalysts in the pyrolysate of lignocelluloses hamper the fermentable utilization of pyrolytic sugars, which need further investigation and improvement to make this process feasible. Graphical abstract: fx1 Highlights: Levoglucosan (LG) from biomass by fast pyrolysis is reviewed in details. Biomass components and structural properties on LG formation are presented. Pretreatment techniques for fast hydrolysis are summarized. Detoxification and hydrolysis of LG for fermentation are introduced. Challenges for LG production and fermentation are proposed.